2022
DOI: 10.1002/1878-0261.13308
|View full text |Cite
|
Sign up to set email alerts
|

Protein palmitoylation in cancer: molecular functions and therapeutic potential

Abstract: Protein S‐palmitoylation (hereinafter referred to as protein palmitoylation) is a reversible lipid posttranslational modification catalyzed by the zinc finger DHHC‐type containing (ZDHHC) protein family. The reverse reaction, depalmitoylation, is catalyzed by palmitoyl‐protein thioesterases (PPTs), including acyl‐protein thioesterases (APT1/2), palmitoyl protein thioesterases (PPT1/2), or alpha/beta hydrolase domain‐containing protein 17A/B/C (ABHD17A/B/C). Proteins encoded by several oncogenes and tumor suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 155 publications
0
17
0
Order By: Relevance
“…In the past decade, the importance of protein palmitoylation in tumorigenesis has become evident. It plays a crucial role in various critical aspects of cancer, such as cell proliferation and survival, cell invasion and metastasis, as well as the modulation of antitumor immune responses . We have reported here that orlistat and palmostatin B are nanomolar inhibitors of PPT1 which are structurally related usingTanimoto similarity (MACCS fingerprints) of 0.65, and both molecules contain a hydrophobic tail and a β lactone ring.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In the past decade, the importance of protein palmitoylation in tumorigenesis has become evident. It plays a crucial role in various critical aspects of cancer, such as cell proliferation and survival, cell invasion and metastasis, as well as the modulation of antitumor immune responses . We have reported here that orlistat and palmostatin B are nanomolar inhibitors of PPT1 which are structurally related usingTanimoto similarity (MACCS fingerprints) of 0.65, and both molecules contain a hydrophobic tail and a β lactone ring.…”
Section: Discussionmentioning
confidence: 91%
“…Palmostatin B is a nonspecific depalmitoylation inhibitor that primarily inhibits the acyl-protein thioesterases APT-1 and APT-2, which, like PPT1, can catalyze the removal of S-palmitoylation from protein substrates . It was earlier demonstrated that the combination of palmostatin B with the FLT3 inhibitor gilteritinib significantly suppressed FLT3-ITD-mediated signaling and leukemia progression .…”
Section: Discussionmentioning
confidence: 99%
“…Fast expanding in the research field of understanding the roles of protein palmitoylation in different types of human malignancies has been achieved in the past decades [39][40][41], however, it was revealed that the linkage between palmitoylation and HCC is relatively weak as compared to other tumor types, e.g. breast cancer, prostate cancer, colorectal cancer, leukemia, melanoma, pancreatic cancer and NSCLC [20,23,[42][43][44][45][46][47][48]. Our current study strengthened the connection that AEG-1, a key driver of HCC, is palmitoylated, which negatively regulates its protein stability via proteasome mediated degradation pathway; inhibiting AEG-1 palmitoylation enhances its binding to SND1 and thus the RISC activity, the latter may downregulate the mRNA level of several tumor suppressors as PTEN/TGFB2 and therefore promotes HCC progression.…”
Section: Discussionmentioning
confidence: 99%
“…To date, 23 mammalian palmitoyl-transferases, namely zDHHCs [16] and 5 depalmitoylating enzymes including APT1/2, PPT1/2 and ABHD17a [17][18][19] have been identified. The link between palmitoylation and various types of human malignancies has been firmly established by the findings that many oncogenes and tumor suppressors are palmitoylated [8,[20][21][22][23], yet, such relationship is labile in HCC.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Altered APT1 activity has been associated with cancer, neurodegenerative diseases, and cardiovascular disorders. [11] Targeted modulation of APT1 could potentially be explored in therapy aimed at addressing these conditions. [9b,12] Moreover, serine hydrolases have been extensively studied using ABPP, benefiting from a comprehensive proteomics toolbox for their analysis.…”
mentioning
confidence: 99%